Bioefficacy and durability of Olyset® Plus, a permethrin and piperonyl butoxide-treated insecticidal net in a 3-year long trial in Kenya - Paul M. Gichuki; Luna Kamau; Kiambo Njagi; Solomon Karoki; Njoroge Muigai; Damaris Matoke-Muhia; Nabie Bayoh; Evan Mathenge; Rajpal S. Yadav (BMC, 2021)
Abstract Background Long-lasting insecticide nets (LLINs) are a core malaria intervention. LLINs should retain efficacy against mosquito vectors for a minimum of three years. Efficacy and durability of Olyset® Plus, a permethrin and piperonyl butoxide (PBO) treated LLIN, was evaluated versus permethrin treated Olyset® Net. In the absence of WHO guidelines of how to evaluate PBO nets, and considering the manufacturer's product claim, Olyset® Plus was evaluated as a pyrethroid LLIN. Methods This was a household randomized controlled trial in a malaria endemic rice cultivation zone of Kirinyaga County, Kenya between 2014 and 2017. Cone bioassays and tunnel tests were done against Anopheles gambiae Kisumu. The chemical content, fabric integrity and LLIN survivorship were monitored. Comparisons between nets were tested for significance using the Chi-square test. Exact binomial distribution with 95% confidence intervals (95% CI) was used for percentages. The WHO efficacy criteria used were ≥ 95% knockdown and/or ≥ 80% mortality rate in cone bioassays and ≥ 80% mortality and/or ≥ 90% blood-feeding inhibition in tunnel tests. Results At 36 months, Olyset® Plus lost 52% permethrin and 87% PBO content; Olyset® Net lost 24% permethrin. Over 80% of Olyset® Plus and Olyset® Net passed the WHO efficacy criteria for LLINs up to 18 and 12 months, respectively. At month 36, 91.2% Olyset® Plus and 86.4% Olyset® Net survived, while 72% and 63% developed at least one hole. The proportionate Hole Index (pHI) values representing nets in good, serviceable and torn condition were 49.6%, 27.1% and 23.2%, respectively for Olyset® Plus, and 44.9%, 32.8% and 22.2%, respectively for Olyset® Net but were not significantly different. Conclusions Olyset® Plus retained efficacy above or close to the WHO efficacy criteria for about 2 years than Olyset® Net (1-1.5 years). Both nets did not meet the 3-year WHO efficacy criteria, and showed little attrition, comparable physical durability and survivorship, with 50% of Olyset® Plus having good and serviceable condition after 3 years. Better community education on appropriate use and upkeep of LLINs is essential to ensure effectiveness of LLIN based malaria interventions. Graphical Abstract